Pengembangan Kombucha Herbal Berbasis Kearifan Lokal sebagai Sediaan Pangan Fungsional dalam Perspektif Farmasi pada Pembelajaran Mata Kuliah Herbal di Program Studi D3 Keperawatan STIKes Tujuh Belas Karanganyar Tahun 2025 - Firman Rezaldi; Yugga Tri Surahman; Hadi Susilo; Erni Suminar; Syariful Mubarok; Maskun Kurniawan (Jurnal Medika: Medika, 2026)
The development of herbal fermentation-based functional foods represents an innovative approach in Herbal course learning within health education. This activity aimed to integrate herbal kombucha production as a case study in the D3 Nursing Program at STIKes Tujuh Belas Karanganyar. A qualitative case study design was applied over one academic semester through planning, implementation, and evaluation stages of practice-based learning. Students produced herbal kombucha using local ingredients such as white turmeric, lemongrass, and temulawak through SCOBY fermentation techniques. Data were collected through observation, semi-structured interviews, and documentation, then analyzed descriptively. The results showed a significant improvement in students’ understanding of functional food concepts, fermentation principles, and the pharmacological potential of local herbs. This hands-on learning approach also encouraged a cognitive transformation from traditional herbal perspectives to modern biotechnology-based understanding. In addition to producing learning products, this activity enhanced students’ scientific literacy in relating fermentation, bioavailability of bioactive compounds, and health benefits. The integration of herbal kombucha proved to be an effective innovative learning model relevant to promotive and preventive competencies in vocational nursing education..